Simón bolívar como escritor (Papeles, 2010)
Many studies have been done about Simon Bolívar, the man and about El Libertador, the hero, but so few specialists have analyzed one of the most fruitful aspects of his life: his writing. This writing should be seen not only as the product of his heoric action, but also as an aesthetic work of literary character. His thoughts, struggles, feelings and desires are stated in his discourses and his personal letters; additionally those writings are full with a new and fresh style in regards to literature of his period, and this means that Bolívar was a real revolutionary in more than one sense.
Keywords: Simón Bolívar; El Libertador; hero; man; thought; feeling; writing; proclamation; letters; critic; neoclassicism; peotical; style; independency; revolution